2020
DOI: 10.1038/s41401-020-0377-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the protective effects of schizandrol A in acute myocardial ischemia mice by comprehensive metabolomics profiling integrated with molecular mechanism studies

Abstract: Schizandrol A (SA) is an bioactive component isolated from the Schisandra chinensis (Turcz.) Baill., which has been used as a remedy to prevent oxidative injury. However, whether the cardioprotective effect of SA is associated with regulating endogenous metabolites remains unclear, thus we performed comprehensive metabolomics profiling in acute myocardial ischemia (AMI) mice following SA treatment. AMI was induced in ICR mice by coronary artery ligation, then SA (6 mg·kg −1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…The functional metabolomics found that N-acetylneuraminic acid was a potential metabolic marker for CAD progression and silencing its regulatory enzyme, neuraminidase-1, might become an unrecognized therapeutic intervention for CAD [ 15 ]. In our previous study, schizandrol A effectively protected AMI mice through upregulation of ecto-5′-nucleotidase, methionine synthase and platelet-derived endothelial cell growth factor based on metabolomics analysis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functional metabolomics found that N-acetylneuraminic acid was a potential metabolic marker for CAD progression and silencing its regulatory enzyme, neuraminidase-1, might become an unrecognized therapeutic intervention for CAD [ 15 ]. In our previous study, schizandrol A effectively protected AMI mice through upregulation of ecto-5′-nucleotidase, methionine synthase and platelet-derived endothelial cell growth factor based on metabolomics analysis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schizandra Chinensis Fructus extracts induce apoptosis via the ROS-mediated/mitochondriadependent pathway and JNK/p38 MAPK activation [89]. In addition, Schizandra Chinensis Fructus was found to facilitate PI3K-AKT activation and inhibit the expression of NOX2 in AMI mice and oxygen-glucose deprivationtreated H9c2 cells [90]. Rehmannia Radix Praeparata had efficient detectable antioxidant activity [91], and the PI3K-Akt and MAPK signaling pathways were found in the pathway analysis for CAD on Rehmannia Radix Praeparata [92].…”
Section: Discussionmentioning
confidence: 99%
“…Laitano's research showed during the recovery period after high-intensity running wheel training, the level of uracil in the myocardium of mice was signi cantly increased, which was essential for myocardial repair after strenuous exercise [36] . Study showed the plasma thymine in mice with acute myocardial ischemia increased signi cantly and the expansion of thymine was closely related to the risk of heart disease [37] . Peng's research showed a signi cant decrease in thymidine in rats' serum can be used as a biomarker of early acute myocardial infarction [38] .…”
Section: Discussionmentioning
confidence: 99%